INFLUENCE OF SALICYLIC ACID PRE-TREATMENT ON WATER STRESS AND ITS RELATIONSHIP WITH ANTIOXIDANT STATUS IN GLYCINE MAX - MEENAKSHI MISHRA; UMESH KUMAR; VEERU PRAKASH (International Journal of Pharma and Bio Sciences, 2013)
The combined effect of salicylic acid (SA) (100, 200 and 400 ppm) and water stress (waterlogging and drought) on growth, reactive oxygen species generation and activities of enzymatic and non-enzymatic antioxidants were studied in soybean (Glycine max L. Merr.) leaves.The results proved that the interaction of salicylic acid with water stress significantly increased total protein content and decreased reactive oxygen species (superoxide anion radical and hydrogen peroxide) in soybean leaves. Water stress also motivated enzymatic (superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR)) and non-enzymatic (carotenoids, ascorbic acid, nonprotein thiol and proline) activity, while they had a declining trend as a consequence of increasing SA level. It showed prominent role of SA and a sign of oxidative damage in experimental models. . Further investigation to evaluate long term water stress effects is recommended.